Spironolactone and eplerenone are cardioprotective during early phase of ischemia in rats submitted to acute coronary occlusion (Research, Society and Development, 2022)
Introduction: Mineralocorticoid receptor antagonists (MRAs) are effective in reducing left ventricle remodeling and sudden death after acute myocardial infarction (AMI). Objectives: MRAs in vitro display cardioprotective effects, independent of MR; however, it is unknown whether the rapid effects of MRAs are cardioprotective in vivo. This study evaluated the acute effects of spironolactone and eplerenone in the first minutes of AMI. Methods: Wistar Rats, submitted or not to bilateral adrenalectomy, were treated orally with spironolactone (20 mg/kg) or eplerenone (10 mg/kg), and submitted to the left coronary ligation, under anesthesia. Electrocardiogram (ECG) recordings were obtained to evaluate ST-T segment, QT, and QTc intervals. Arterial pressure was also measured before (baseline) and after coronary ligation. Results: Spironolactone or eplerenone given, one hour before coronary ligation, prevented ST-T segment elevation in adrenalectomized and non-adrenalectomized. QT interval analysis showed that MRAs prevented its prolongation after coronary ligation. QT and QTc intervals remained similar to baseline and were smaller than the values displayed by the non-treated group. Animals treated with spironolactone, regardless of adrenalectomy, showed a 3-fold reduced mortality rates compared to the control group. Conclusion: MRAs display acute cardioprotective effects in early phase of AMI, which are independent of aldosterone.